2020
DOI: 10.1093/jn/nxaa184
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Urinary Biomarker Approach Reveals Widespread Exposure to Multiple Low-CalorieSweeteners in Adults

Abstract: Background Observational investigations into the health impacts of low-calorie sweeteners (LCSs) in humans fail to adequately identify or fully characterize LCS consumption. Objectives We aimed to utilize a novel biomarker approach to investigate exposure to 5 LCSs and to test whether reported low-calorie sweetened beverage (LCSB) consumption effectively identifies exposure to LCSs in adults. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The systematic literature search strategy yielded 1130 non-duplicated records from the four electronic databases. After abstract reading, full text reading for eligibility assessment, and secondary search, 17 studies were included [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The systematic literature search strategy yielded 1130 non-duplicated records from the four electronic databases. After abstract reading, full text reading for eligibility assessment, and secondary search, 17 studies were included [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ], as shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the study characteristics and candidate biomarkers identified. There were eight cross-sectional studies [ 29 , 30 , 33 , 34 , 36 , 38 , 39 , 44 , 45 ] and eight controlled intervention studies [ 31 , 32 , 35 , 37 , 40 , 41 , 42 , 43 ]. For comparison with dietary intake, dietary assessment tools such as 24-h recall, 4-day and 7-day food records, and FFQS were used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One major limitation of this study was the inability to evaluate the actual content of LNCS to be able to estimate dietary intakes. In this regard, biomarker analysis could be combined with dietary assessment as suggested by Logue et al ( 28 ), who used a novel urinary biomarker approach for the determination of up to five LNCS to characterize consumption in adults.…”
Section: Discussionmentioning
confidence: 99%